PENGEMBANGAN DAN ANALISIS SOAL HIGHER ORDER THINKING SKILLS BERBASIS ALAM DAN BUDAYA PAPUA - Tanujaya, Benidiktus; Mumu, Jeinne (Journal of Honai Math, 2020)
Higher Order Thinking Skills of students in Indonesia, including students in Papua, are still very low. On the other hand, Papua's nature and culture have the potential to be used as an instrument or context in developing questions that can develop students' Higher Order Thinking Skills (HOTS), especially in mathematics learning. This study aims to create and analyze HOTS questions based on nature and culture. The products developed were HOTS items, with the procedure for determining the context, expanding the items, testing the items' validity, and further analysis. The results showed that HOTS mathematics questions could be developed using Papua's Nature and Culture context. These results contribute to inspiring educators and other researchers to establish HOTS questions based on Papua's nature and culture, both in mathematics and other subjects.